Analisis Struktur Batin Pada Puisi Selamat Ulang Tahun Buku Karya Joko Pinurbo - Muhammad Rizqi Fatahilah; Suci Ika Pujowati; Heru Widhi Handayani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Poetry is one of the most interesting forms of literary work but is full of meaning. Poetry is a medium for conveying feelings and ideas with beautiful words. Poetry as a meaningful aesthetic work is also a recording and interpretation of human experience composed in the most memorable form. Poetry can make us laugh, cry, smile, think, reflect, be moved and even get emotional and angry. Until now, poetry can be an illustration of the cultural progress of society. How the writer of the poem views his world is a real picture of the culture that surrounds him. Because the progress of society from time to time always increases, bringing changes in the style, nature and form of poetry. Poetry changes following developments in taste, ever-changing aesthetic concepts, and intellectual progress. The aim of the research is stated in a sentence that explores or deepens the inner structure of poetry. The inner structure intended is: theme, tone, feeling and message. The method used in this research is descriptive analytical method. This method also attempts to describe facts logically. Through this method, the researcher tries to analyze the inner structure of Joko Pinurbo's poem entitled